Integrasi Tasawuf dan Psikologi Positif dalam Mengelola Kecemasan Eksistensial pada Generasi Z di Era Digital - Khusnul Khotimah; Khoirunissa Wibowo (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This research examines the integration of Sufism and positive psychology approaches as interventions to manage existential anxiety in Generation Z in the digital era. Existential anxiety, characterized by questions about life's meaning, death, and self-authenticity, is increasing in the generation that has grown up in the digital technology era. Through a qualitative approach with phenomenological methods, this study involved 30 Generation Z participants (18-25 years old) experiencing existential anxiety. The results show that Sufi practices such as dhikr, muhasabah, and tazkiyatun nafs combined with positive psychology interventions such as mindfulness, gratitude practice, and strength-based approach can improve psychological well-being, reduce existential anxiety, and build deeper meaning in life. The integration of these two approaches provides a holistic framework that combines Islamic spirituality with modern psychological science to address the psychological problems of the digital generation. The implication of this research is the development of an intervention model based on local wisdom and spirituality for the mental health of young people in the digital era.